Penerapan Permainan Bola Beracun pada Awal Pembelajaran Pjok untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas IX di SMPN 13 Surabaya - Mochammad Ilmawan Amiruddin; Andhega Wijaya; Agus Suparno (Journal of Creative Student Research, 2024)
This research was motivated by the low learning motivation of students in class IX of SMP Negeri 13 Surabaya. The aim of this research is to obtain data and information regarding increasing students' learning motivation by implementing a small poison ball game in PJOK learning. The type of research used is classroom action research with planning, implementation, observation and reflection procedures. Classroom action research was conducted in class IX at SMP Negeri 13 Surabaya with a total of 30 students. The research was carried out over two cycles and data collection on student learning motivation was carried out through motivation questionnaires, interviews and documentation and then analyzed using descriptive quantitative percentages. The research results obtained an increase in student motivation obtained from the motivation questionnaire conducted at the end of cycles I and II by filling in the questionnaire on reflection on PJOK learning.